Mutagenesis of SlNAC4 by CRISPR/Cas9 alters gene expression and softening of ripening tomato fruit - Ying Gao; Yi-Ping Zhang; Zhong-Qi Fan; Yuan Jing; Jian-Ye Chen; Donald Grierson; Rui Yang; Da-Qi Fu (Vegetable Research)
Softening is one of the key fruit quality traits, which results from the selective expression of cell wall metabolism genes during ripening. The identification of transcription factors (TFs) that regulate fruit softening is an important field in order to understand and control fruit softening. In tomato, NAC (NAM, ATAF, and CUC) TFs members have been demonstrated to be involved in fruit ripening regulation, including NAC-NOR (non-ripening), NOR-like1, SlNAC4, SlNAC1. Here, we generated slnac4 mutant knockout (CR-SlNAC4) tomato plant by a clustered regularly interspaced short palindromic repeats genomic targeting system (CRISPR/Cas9) and SlNAC4 overexpressing (OE-SlNAC4) plant. In addition to confirming the previously reported results that SlNAC4 positively regulates fruit ripening, we found that SlNAC4 has a strong effect on tomato fruit softening. Compared with the control fruit, fruit softening was inhibited in slnac4 fruit and conversely was accelerated in OE-SlNAC4 tomato fruit. Through RNA-sequencing (RNA-seq) analysis, we found that expression levels of SlEXP1 (expansin) and SlCEL2 (endo-β-1,4 glucanase) genes involved in cell wall metabolism were significantly different in WT (wild type)/slnac4 and WT/OE-SlNAC4 fruit. Further study showed that these genes contained a NAC TF binding domain in their promoter regions. In vitro electrophoretic mobility shift assays (EMSA) and dual-luciferase reporter assays (DLR) demonstrated that these two genes were the direct targets of SlNAC4 binding and transactivation. The results enriched the function of SlNAC4 and provided a new dimension in understanding the regulation of tomato fruit softening.